Enhanced Version Control for Unconventional Applications - (:unkn) unknown (My University, 2017)
The Extensible Markup Language (XML) is widely used to store, retrieve, and share digital documents. Recently, a form of Version Control System has been applied to the language, resulting in Version-Aware XML allowing for enhanced portability and scalability. While Version Control Systems are able to keep track of changes made to documents, we think that there is untapped potential in the technology. In this dissertation, we present novel ways of using Version Control System to enhance the security and performance of existing applications. We present a framework to maintain integrity in offline XML documents and provide non-repudiation security features that are independent of central certificate repositories. In addition, we use Version Control information to enhance the performance of Automated Policy Enforcement eXchange framework (APEX), an existing document security framework developed by Hewlett-Packard (HP) Labs. Finally, we present an interactive and scalable visualization framework to represent Version-Aware-related data that helps users visualize and understand version control data, delete specific revisions of a document, and access a comprehensive overview of the entire versioning history.
Keywords: Apex; Document Engineering; Information Security; Integrity; Non-repudiation; Visualization